First case of centric fission in a Murrah buffalo bull - B. Prakash; Deepika; Satbir Singh (Journal of Livestock Biodiversity, 2025)
Reduced fertility in humans and domestic animals has been associated with cytogenetic abnormalities. Examinations during the last four decades of the chromosome complements of various species of domestic animals have revealed the existence of a considerable number of chromosomal abnormalities. Routine cytogenetic investigations, in this study, of cattle and river buffalo males allocated for breeding revealed the presence of higher somatic chromosome number (51) than the normal (50) in all the cells of a young, normal-looking river buffalo bull selected for reproduction. Analysis of the somatic chromosome number, karyotypic features and morphology of chromosomes established that the enhanced chromosome number was the consequence of centric fission of chromosome 1. Though centric fission has been observed in a range of organisms and has been ascribed an important role in karyotype evolution, the present case is only the first incidence of centric fission in buffaloes.